Coleções entomológicas como ferramenta pedagógica na transformação das representações sociais sobre a diversidade dos insetos - Oliveira, Rubens Coutinho Soares (Universidade Federal de São Carlos, 2026)
This study investigated the contributions of building entomological collections as an active pedagogical strategy for transforming the negative social representations of elementary school students about insects. The qualitative-quantitative research was conducted with 23 seventh-grade students from a public school in São Carlos, São Paulo, using pre- and post-intervention questionnaires to map changes in affective, conceptual, and taxonomic dimensions.Based on Moscovici's Theory of Social Representations and Abric's structural approach, as well as Costa Neto's Ethnoentomology and Paulo Freire's pedagogy of autonomy, the study initially diagnose da strong “Entomoprojective Ambivalence,” where feelings of disgust and fear predominated, associated with a negative utilitarian view and taxonomic errors. The results obtained after the collection assembly workshop revealed a significant reversal in the affective polarity of the class: the feeling of “Disgust” was drastically reduced, giving way to “Curiosity,”which became the dominant feeling, although “Fear” remained stable, suggesting the resistance of the central core of the representation. In the cognitive sphere, a qualitative leap was observed in the morphological accuracy of the drawings and a 76.32% reduction in taxonomic identification errors,indicating the overcoming of the “insect” ethnocategory. Furthermore, there was a transition in functional perception, which shifted from the notion of “harmfulness/uselessness” to an “Ecological Systemic” understanding. It can be concluded that the direct and technical manipulation of specimens acted as an effective mediating device in the flexibilization of the peripheral system ofsocial representations, allowing students to transition from naive curiosityto epistemological curiosity, reconfiguring their relationship with biodiversity from one of extermination to one of scientific investigation and respect.
Entomological collections as a pedagogical tool in the transformation of social prepresentations about insect diversity
Keywords: ensino de ciências; coleção entomológica; representações sociais; educação ambiental; metodologias ativas; CIENCIAS BIOLOGICAS::ZOOLOGIA; 15. Vida Terrestre